Patterns of presentation of abused children to the accident and emergency department. - Olney, D B (1988)
A search of accident and emergency department records showed that 61% of 85 children registered as being physically or sexually abused by the Department of Community Paediatrics at St James's University Hospital, Leeds, England, were found to have visited the accident and emergency department an average of 2.9 times before the diagnosis was made. Fifty-two per cent of the attendances were because of problems other than injuries. Staff of accident and emergency departments should be aware that abused children present with medical diagnoses as well as trauma. Increased awareness may result in earlier diagnosis of abuse in some of these children.